Assessment of Wind Energy Potential for Small Scale Power Generation at Thatta, Sindh, Pakistan - S.Z. Abbas; R. Tanweer; Firoz Ahmad; Fayyaz ur Rasheed; Junaid Karim; Alay Raza (Journal of Basic & Applied Sciences, 2015)
In this paper, the wind characteristics and wind Power potential for south coast of Thatta, Sindh province, Pakistan are presented. The variation of monthly wind speed at the height of 10m, 20m, 30m, 40m, and 50m are presented. The power density for these heights are calculated employing coefficient of performance Cp as 0.40 and 0.45. Season wise classification of wind speed and power density at these heights indicates a fairly reasonable prospect of wind energy utilization for small scale power generation.